Play & Control. - Belenoti-Bellot, Marie; Broucke, Koen; Coissard, Elisa; Collieux, Julien; Domènech, Antonio; Jessen, Joseph; Rattemeyer, Volker; Rau, Tanja; Tihinen, Juha-Heikki; Velikova, Tereza (Pori : Pori Art Museum, 2002)
The Play & Control exhibition at the Pori Art Museum explores the creative process and the control of performing that revises it. The exhibition presents eight young artists who have realized works on the concept of playing and who question the traditional implications associated to a work of art. A starting point for the artists is the playing child. The creative process itself comes very close to a young child's play, free and without obligations. By giving the play a structure the play is given function that moulds it into a certain direction. The desire to play (the precondition for every creative process) and the necessity to have a legitimated form directed by the unwritten rules and regulations of the art world are constantly in tension. To what extent should the artist be presented to compromised ? How far will the real game go ?
Fins & Engels
Play & Control, Pori Art Museum, Pori, 22.03.2002 - 02.06.2002 Germinations 13
boek
Keywords: Bourcereau, Alice; Belenotti-Bellot, Marie; Coissard, Elisa; Collieux, Julien; Jessen, Joseph; Naveau, Nadia; Rau, Tanja; Velikova, Tereza